Perioperative Propranolol Against Dental Anxiety: A Randomized Controlled Trial - Steenen, Serge A.; Su, Naichuan; van Westrhenen, Roos; van Wijk, Arjen J.; Tjia, Daniël S. L.; de Lange, Jan; de Jongh, Ad (Frontiers in Psychiatry, 2022)
Background: Promising results from trauma reactivation studies on post-traumatic stress disorder suggest that propranolol is capable of attenuating symptoms of traumatically induced mental disorders by blocking memory reconsolidation. Methods: A randomized, parallel, placebo-controlled, quadruple-blind trial, was designed to determine the effectiveness of perioperative propranolol during exposure to dental extractions in reducing dental anxiety in patients with dental anxiety or dental phobia. Between November 2014 and December 2018, 52 patients with high levels of fear in anticipation of dental extractions who were referred to a department of oral and maxillofacial surgery for at least two tooth and/or molar removals with one month in between were included. On the first visit participants received either 120 mg of perioperative oral propranolol (n = 19) or placebo (n = 17), and a core fear memory was reactivated one hour preoperatively. The primary outcome was change in severity of dental anxiety from baseline to one-month follow-up, as indexed by the short version of the dental anxiety inventory (S-DAI). Secondary outcome measures were change in intra-operative state anxiety and specific phobia diagnoses. Results: Linear mixed model (LMM) yielded no statistically significant difference in change of dental trait anxiety from baseline to 1-month follow-up between propranolol and placebo groups (Cohen’s d = 0.23). S-DAI scores decreased in both study arms from baseline to follow-up (propranolol arm: from 32.1 [SD=7.3] to 29.1 [SD=8.8]; placebo arm: from 31.6 [SD=7.5] to 27.1 [SD=6.5]). Also, administering propranolol was not associated with a significant difference in change of intra-operative state anxiety or phobia diagnoses between groups over time. Conclusions: The results do not concur with earlier findings regarding post-traumatic stress disorder, and suggest that individuals with traumatically induced fears or phobias do not benefit from the application of perioperative propranolol. Trial registration: ClinicalTrials.gov, identifier: NCT022683570.